Investigação da evolução dos pólipos endometriais em câncer de endométrio - Peres, Gustavo Filipov [UNESP] (2015)
Objective: To evaluate the immunohistochemical expression of estrogen receptors (RE), progesterone receptors (RP), cell proliferation (Ki-67), neoangiogenesis (endoglin - CD105), cell adhesion (claudin 3 and 4) and extracellular matrix proteins (metalloproteinases 2 and 9 - MMP 2 and MMP 9) in endometrial polyps and endometrial cancer compared to normal endometrium. Design: Comparative cross-sectional study with occasional sample. The survey was conducted from the database of the Clinical Pathology Laboratory of Botucatu Medical School - Unesp. Setting: Clinics Hospital from Botucatu Medical School, São Paulo State University - UNESP. Patients: Were performed immunohistochemical studies of 30 samples of endometrial polyps without atypia and 30 samples of endometrioid adenocarcinoma of endometrium confronted with the results of 30 normal endometrial samples (control group). Interventions: Epidemiological, clinical and anthropometric data were collected through analysis of medical records. To analyze the cases of endometrial adenocarcinoma and controls we used the tissue microarray technique (TMA). Paraffin blocks, with the larger fragment of polypoid lesions and recipient blocks of TMA were used to evaluate immunohistochemical expression of ER, PR, CD105, Ki-67, claudin 3 and 4, MMP-2 and MMP-9. Main Results: We identified a significant difference between groups in ER (P <0.001) and PR expression (P<0.05), Ki-67 (P<0.001), CD105 (P<0.001) and claudin 3 (P<0.001). No difference was found between polyps and endometrial cancer (P≥0,05). The expression of MMP-2 and MMP-9 was virtually absent in all three groups. Conclusions In the studied samples according to the immunohistochemical parameters evaluated no differentiation between polyps and endometrial cancer was observed. There was no expression of MMP-2 and -9 in endometrial tissues analyzed. Further studies are necessary to better understand ...